Evaluation of machining performance with micro size tool tip - Ong, Chin You. (2010)
The surface finish quality of a machined part is affected by the machine tool accuracy, cutting tool quality and dynamic machining effects. The aim of this report is to investigate and discuss the pre-requisite parameters for the micro-cutting process to fabricate Fresnel Lens. The interaction between the properties of the material and the process parameters on the fabrication result will be investigated based on the experimental and theoretical results. The cutting experiments of aluminum alloy (Al6061) and Oxygen Free Copper (OFC) were performed with various parameters such as feed rate, cutter nose radius, steepness of the cutting profile, etc. in order to investigate the effect of these parameters on the machined surface integrity. The experiments were carried out on an ultra-precision 5-axis CNC lathe machine with single crystal diamond cutting tool. Through the experiment, the surface finish was found to be improving with decreasing of the feed rate subject to the condition of the feed rate never going below the critical chip thickness value. If the feed rate was reduced below the critical chip thickness value, ploughing could occur and affect the surface finish quality. Comparing between Aluminum AL6061 with Oxygen-Free Copper (OFC), OFC appear to be a higher purity material with less impurities and inclusion, thus it was capable of achieving better surface finish quality. Apart from that, the steepness of the machine profile would also affect the surface finish of a fabricated part. As the steeper the slope became, more segmentation with shorter length would be generated by the CNC interpolator. This will result in an unstable cutting feed rate along the slope which leads to deterioration of the smoothness of the slope and surface quality. Lastly would be the cutter nose radius effect on the surface finish.